BTT211 I BTT306- Techniques in Biotechnology (Teknik Biotekno/ogi) - PPSKJ, Pusat Pengajian Sains Kajihayat (Pusat Pengajian Sains Kajihayat, 2024)
First Semester Examination 2023/2024 Academic Session February 2024 BTT211 I BTT306- Techniques in Biotechnology (Teknik Biotekno/ogi) Duration: 2 hours (Masa: 2 jam)